An overview of the ameliorative efficacy of Catharanthus roseus extract against Cd2+ toxicity: implications for human health and remediation strategies - Hashim, Mohammad; Arif, Hussain; Tabassum, Baby; Rehman, Shahnawaz; Bajaj, Priya; Sirohi, Rekha; Khan, Mohd Faizan Ali (Frontiers in Public Health, 2024)
Rapid industrialization has led to an increase in cadmium pollution, a dangerously toxic heavy metal. Cadmium (Cd) is released into the environment through industrial processes and can contaminate air, water, and soil. This pollution poses a significant risk to human health and has become a pressing concern in many industrialized areas. Due to its extended half-life, it leads to a range of health problems, including hepato-nephritic toxicity, brain damage, and degenerative bone disorders. Intoxication alters various intracellular parameters, leading to inflammation, tissue injury, and oxidative stress within cells, which disrupts normal cellular functions and can eventually result in cell death. It has also been linked to the development of bone diseases such as osteoporosis. These adverse effects highlight the urgent need to address cadmium pollution and find effective solutions to mitigate its impact on human health. This article highlights the Cd-induced risks and the role of Catharanthus roseus (C. roseus) extract as a source of alternative medicine in alleviating the symptoms. Numerous herbal remedies often contain certain bioactive substances, such as polyphenols and alkaloids, which have the power to mitigate these adverse effects by acting as antioxidants and lowering oxidative cell damage.Research conducted in the field of alternative medicine has revealed its enormous potential to meet demands that may be effectively used in safeguarding humans and their environment. The point of this review is to investigate whether C. roseus extract, known for its bioactive substances, is being investigated for its potential to mitigate the harmful effects of cadmium on health. Further investigation is needed to fully understand its effectiveness. Moreover, it is important to explore the potential environmental benefits of using C. roseus extract to reduce the negative effects of Cd. This review conducted in the field of alternative medicine has revealed its enormous potential to meet demands that could have significant implications for both human health and environmental sustainability.